Prospects for the Discovery of General Dark Matter-Induced Atomic Responses - Lindroos, Oskar (My University, 2020)
One of the major mysteries of modern physics is dark matter. Proposed by Fritz Zwicky in 1933, dark matter stands as the answer to several astronomical observations, but its constituents remain unkown. Since current observations only show dark matter interacting gravitationally, one can assume that the dark matter particle is a massive, weakly interacting particle also referred to as a WIMP. In an attempt to find the dark matter particle, large underground detectors have been constructed. These detectors utilise the principle of direct detection in order to detect weakly interacting particles. As the Earth passes through the halo of dark matter within the Milky Way one expects the flux of dark matter particles that arises to produce a signal within these experiments. However, so far a signal that cannot be anything other than dark matter remains to be found. This thesis will present the sensitivities for future direct detection experiments under the assumption of general dark matter-electron interactions. We provide the underlying theory of a model describing general dark matter-electron interactions in the non-relativistic frame which we use to simulate event rates in active experiments. Based on the null results in current experiments, we perform a statistical analysis in order to find the lowest detectable coupling constant for different sets of interactions corresponding to a specific dark matter particle mass. We express the sensitivity of future direct detection experiments in terms of statistical significance for signal discovery.
Keywords: dark matter; direct detection; statistical significance; projected sensitivity